Memory Reactivation and Its Effect on Exercise Performance and Heart Rate - Dhawan, Abhishek G. (Frontiers in Sports and Active Living, 2020)
Neuronal ensemble and brain plasticity plays an important role in memory consolidation and subsequently memory reactivation. Till date many studies have been designed to study effect of exercise, heart-rate variability and other factors on brain plasticity and memory. We present a case study in which we demonstrate effect of neuronal ensemble and memory formed during High intensity aerobic training (VO2 max) and Target Heart-Rate (THR) training and the effect of reactivation of same memory on THR and performance. Noteworthy: The reactivation and recreation of memory stimulus learned and formed during High intensity training like place, time, odor and other conditions can elevate THR to same previous peak zone even in low intensity. This demonstrates that reactivation of previously acquired memory or using stimulation of neuronal ensemble of consolidated memory during specific event of training may exert same physiological effect on exercise or body learned during memory acquisition phase. Hence as exercise has effect on memory, the memories may have effect on exercise performances.